2016
DOI: 10.1155/2016/6171658
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B: A Double‐Edged Sword in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a spectrum of liver lesions ranging from hepatic steatosis, nonalcoholic steatohepatitis, hepatic cirrhosis, and hepatocellular carcinoma. The high global prevalence of NAFLD has underlined the important public health implications of this disease. The pathogenesis of NAFLD involves the abnormal accumulation of free fatty acids, oxidative stress, endoplasmic reticulum (ER) stress, and a proinflammatory state in the liver. Schisandrin B (Sch B), an active dibenzooctadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…Schizandrin B is an active dibenzocyclooctadiene lignan isolated from the fruit of Schisandra chinensis (a traditional Chinese herb), and was found to possess antioxidant, anti-apoptotic, anti-inflammatory and cardioprotective activities in vitro and in vivo ( 38 , 39 ). Studies indicated that schizandrin B could improve cardiac function and mitigate myocardial infarct size in a MIRI model via inhibiting cell apoptosis and attenuating oxidative stress ( 15 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schizandrin B is an active dibenzocyclooctadiene lignan isolated from the fruit of Schisandra chinensis (a traditional Chinese herb), and was found to possess antioxidant, anti-apoptotic, anti-inflammatory and cardioprotective activities in vitro and in vivo ( 38 , 39 ). Studies indicated that schizandrin B could improve cardiac function and mitigate myocardial infarct size in a MIRI model via inhibiting cell apoptosis and attenuating oxidative stress ( 15 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the three isoforms of Sch, Sch B attracts particular attention. Previous reports revealed Sch B function in neuroprotection by reducing oxidative stress [9,10]. In this review, we describe the pivotal role of Sch B in treating cancers, cardiovascular diseases, and neurodegenerative diseases and explain the molecular mechanism as well as the function in several illnesses.…”
Section: Introductionmentioning
confidence: 94%
“…Schisandrin B (Sch B), is an active dibenzooctadiene lignin that can be isolated from the fruit of Schisandra chinensis (a traditional Chinese herb) ( 5 ). In previously published studies, Sch B was demonstrated to play a crucial role in the treatment of cardiovascular and neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%